2003
DOI: 10.1093/jn/133.10.3166
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Folic Acid–Fortified Bread Improves Folate Status in Women of Reproductive Age in Chile

Abstract: Since January 2000 the Chilean Ministry of Health has required the fortification of wheat flour with folic acid (FA) at a concentration of 2.2 mg FA/kg in order to reduce the risk of neural tube defects (NTD) in newborns. This policy was expected to result in a mean additional intake of approximately 400 microg FA/d. We assessed the effectiveness of the FA flour fortification program on bread folate content and on blood folate concentration in women of childbearing age in Santiago, Chile. The prefortification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
134
1
15

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(156 citation statements)
references
References 15 publications
6
134
1
15
Order By: Relevance
“…There is evidence suggesting that maternal body water near term is an important variable influencing birth weight 34 . Changes in gestation duration were not observed in any of the above-mentioned trials that used a combination of micronutrients in mostly healthy women [8][9][10]28 . Omega-3 fatty acids in this trial may account for the observed statistically significant longer gestation duration.…”
Section: Discussionmentioning
confidence: 91%
“…There is evidence suggesting that maternal body water near term is an important variable influencing birth weight 34 . Changes in gestation duration were not observed in any of the above-mentioned trials that used a combination of micronutrients in mostly healthy women [8][9][10]28 . Omega-3 fatty acids in this trial may account for the observed statistically significant longer gestation duration.…”
Section: Discussionmentioning
confidence: 91%
“…However, a recent study in Mexico in 117 women of reproductive age reported a deficiency of erythrocyte folate and vitamin B 12 of 28 and 20%, respectively (Casanueva et al, 2000). Chile deserves special mention with a successful wheat flour fortification program that has been evaluated recently and resulted in an important decrease of folic acid deficiency (Bunout et al, 1998;Hertrampf et al, 2003). Other countries such as Spain, Cuba and Poland, with important socioeconomic differences, are affected by a high prevalence of folic acid and vitamin B 12 deficiencies (OPS, 1999;Wartanowicz et al, 2001;Planeéis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, a study conducted on 38,000 women in Ontario showed an increase in red blood cell folate from 527nmol/l to 741 nmole/l after food fortification (p<0.001) (Ray et al, 2002). In Chile, the mean serum concentrations and red blood cell folate increased respectively from 9.7 and 290nmol/l to 37.2 and 707nmol/l (p<0.0001) after mandatory fortification (Hertrampf et al, 2003).…”
Section: Fortification Of Food With Folic Acidmentioning
confidence: 99%